Optimal Redistributive Taxation when Government's and Agents' Preferences Differ - Sören Blomquist; Luca Micheletto (Uppsala University, Department of Economics, 2005)
Paternalism, merit goods and specific egalitarianism are concepts we sometimes meet in the literature. The thing in common is that the policy maker does not fully respect the consumer sovereignty principle and design policies according to some other criterion than individuals preferences. Using the self-selection approach to tax problems developed by Stiglitz (1982) and Stern (1982), the paper provides a characterization of the properties of an optimal redistributive mixed tax scheme in the general case when the government evaluates individuals well-being using a different utility function than the one maximized by private agents.
urn:nbn:se:uu:diva-79596
Keywords: H21; H23; 330; optimal taxation; behavioral economics; paternalism; merit goods; non-welfarism; Optimale Besteuerung; Einkommensumverteilung; Steuersystem; Meritorische Güter; Theorie